2000
DOI: 10.4049/jimmunol.164.7.3855
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of Mast Cells in the Development of Airway Hyperresponsiveness in a Murine Asthma Model

Abstract: Immunization of BALB/c mice with alum-adsorbed OVA, followed by three bronchoprovocations with aerosolized OVA, resulted in the development of airway hyperresponsiveness (AHR) and allergic inflammation in the lung accompanied by severe infiltration of eosinophils into airways. In this murine asthma model, administration of monoclonal anti-IL-5 Ab before each Ag challenge markedly inhibited airway eosinophilia, but the treatment did not affect the development of AHR. Immunization and aerosol challenges with OVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
136
4
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 38 publications
6
136
4
5
Order By: Relevance
“…Recently, strong evidence has been presented that ties the role of mast cells in murine models of asthma to the experimental protocols used. Thus, Kobayashi et al (17) noted that mast cell-deficient mice developed reduced AHR compared with normal congenic mice only under certain experimental conditions. They proposed that AHR could be induced by different mechanisms, and only certain protocols would enlist mechanisms that involve IgE-mediated mast cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, strong evidence has been presented that ties the role of mast cells in murine models of asthma to the experimental protocols used. Thus, Kobayashi et al (17) noted that mast cell-deficient mice developed reduced AHR compared with normal congenic mice only under certain experimental conditions. They proposed that AHR could be induced by different mechanisms, and only certain protocols would enlist mechanisms that involve IgE-mediated mast cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…While some reports have demonstrated that mast cell deficiency results in attenuated eosinophilic airway inflammation (10,11), others have shown that this deficiency does not affect allergic airway inflammation and AHR (12)(13)(14)(15). Recent studies have suggested that the extent to which mast cells contribute to airway inflammation and AHR in mice is highly dependent on the experimental model used to generate the airway response (16,17).…”
mentioning
confidence: 99%
“…Some reports have demonstrated that mast cell activation results in a potentiation of late AHR [8][9][10], and mast cells have been reported to represent a potential source of TNF-a in vitro [11,12]. These findings suggest that TNF-a plays a role in mast cellmediated late AHR.…”
Section: Introductionmentioning
confidence: 83%
“…While some reports have demonstrated that mast cell activation results in a potentiation of late AHR [8][9][10], others have shown that AHR can be elicited in the absence of IgE Ab [17,18] or mast cells [19], dependent on the experimental model used to generate the airway response. These data have come from studies that used a protocol that consists of airway antigen challenge for more than 3 consecutive days, and examination of AHR usually 2 days after the last antigen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…При аллергической БА пролиферация Th2 лимфоцитов и синтез интерлейки-на (Interleukin, IL) 4 активированными тучными клетка-ми способствует переключению изотипа В лимфоцитов на синтез иммуноглобулина (Immunoglobulin, Ig) E. С пози-ций современных данных, активация тучных клеток анти-телами IgE не ограничивается реакцией немедленного типа при встрече с установленным аллергеном. Тучные клетки играют важную роль в развитии хронического воспаления дыхательных путей, опосредованного синте-зом IL4, IL5 и IL13, которые в свою очередь стимулируют пролиферацию Th2 лимфоцитов, дальнейший синтез IgE-антител, рекрутирование и дифференцировку эозинофи-лов [10]. Установлено, что инфильтрация респираторного тракта дыхательных путей эозинофилами и последующая их дегрануляция сопровождаются высвобождением цито-токсических продуктов (эозинофильные катионные бел-ки, нейротоксины, пероксидазы), которые вносят зна-чительный вклад в повреждение эпителия дыхательных путей, гиперпродукцию слизи бокаловидными клетками, бронхиальную гиперреактивность и нарушение функ-ции мерцательного эпителия.…”
Section: актуальностьunclassified